Effect of TDZ and BAP on shoot proliferation from in vitro shoot tips of strawberry - Haddadi, Fatemeh; Abdul Aziz, Maheran; Saleh, Ghizan; Abdul Rashid, Azmi; Kamaladini, Hossein (Sarawak Biodiversity Centre, 2008)
An experiment was conducted to induce shoot proliferation from shoot tips derived from runner tips of strawberry cv. Camarosa. The shoot tips were cultured on Murashige and Skoog (MS) medium supplemented with TDZ and BAP, either alone or in combination. The concentrations used were 0 to 8 μM TDZ and 0 to 27 μM BAP. MS medium supplemented with a moderate concentration of 4 μM BAP in combination with 2 μM TDZ was optimum for strawberry shoot proliferation from shoot tips derived from runner tips. In this combination of cytokinins, a 100 % shoot proliferation with a mean number of 14.6 shoots per explant was produced. This regeneration protocol is suitable for mass propagation of planting materials for commercial cultivation of strawberry and for the recovery of transgenic strawberry plants following genetic transformation.